Assessing China’s Power
XIV, 299 p. 13 illus.
Keywords: The topic of China's rise and what it really means for the global and regional order is the subject of intense debate. In this volume, top scholars address China's power today, compare China's power with that of the USA, and forecast China's power in 2025.